EVALUASI KINERJA GURU DALAM PENINGKATAN MUTU DI YAYASAN AL KENANIYAH JAKARTA TIMUR - mas ning zahroh (Universitas Negeri Jakarta, 2021)
Abstrak : Theoretically the results of the discussion of this research is expected to provide scientific contributions to the development of science, to provide some suggestions to the school and other schools in terms of teacher performance in improving the quality of education, to be the evaluation for Yayasan Pondok Al Kenaniyah to provide better service in the quality of their education. This study is also expected to be the contribution for the researcher in the field of education. This study uses a qualitative method of data collection. The data is achieved by conducting interviews, observation and checklist. The data is obtained to analyze the performance of teachers in improving the quality of education with the subject of 60 people in Yayasan Al Kenaniyah, East Jakarta to investigate. Based on the data obtained can be summarized as follows: regarding to the performance of teachers in the learning plan, the performance of teachers in the implementation of learning, the performance of teachers in the assessment of learning outcomes, also discipline of the teachers in performing their duties to get good performance. Thus, the quality of education will be better in the future.